MINOXIDIL AND NEOPTIDE TOPICAL APPLICATION REINFORCED BY LOW-LEVEL LASER THERAPY ON AN ANIMAL MODEL OF ALOPECIA - ORĂSAN, Meda Sandra; CONEAC, Andrei; MIHU, Carmen Mihaela; MARE, Codruţa; MURESAN, Adriana (Studia Universitatis Babeș-Bolyai Chemia, 2015)
This study investigated on a rat model the hair regrowth effects of Low-Level Laser Therapy as monotherapy or concomitant therapy with topical application of two chemical treatments that are used in human patients with hair loss: Minoxidil 2% - Hairgrow (Dar Al Dawa Pharma/Amman, Jordan) and Neoptide (Ducray/ Boulogne, France). Results of hair regrowth evaluated by macroscopical images (photographs), trichoscopy (with a dermatoscope) and grown hair weight (from a surface area of 1cm²) revealed that Minoxidil 2% therapy was more efficient than Neoptide. Topical treatments were less efficient than LLLT exposure alone. Both combined therapies: LLLT plus Minoxidil 2% and LLLT with Neoptide induced better hair regrowth than topical applications. Our study proves that not all the products recommended for human use have the same hair regrowth efficiency on an animal model and that a combined therapy (laser plus topical substance) may bring supplementary benefits.